Arhaična poezija o smrti - Ferkolj, Andrej (Primerjalna književnost, 2004)
Archaic poetry on death. This article is of a multidisciplinary character, intended as a combination of anthropological, literary and philosophical approaches. At the begining it describes some of the general characteristics of archaic poetry and questions the issue of its "literariness". Afterwards, based on Gadamer's hermeneutic model of comprehension, it analyses archaic poetry containing themes of death. After the reconstruction of the original horizon, it deals with the interpretation that corresponds to some aspects of Heidegger's philosophy, and concludes with an appeal to a hermeneutic application of the findings.
Keywords: literarna veda; literary science; kulturna antropologija; hermenevtika; ljudsko pesništvo; ustno slovstvo; arhaična poezija; death; smrt